Penerapan Video Sebagai Media Pembelajaran pada Pembelajaran Pjok Kelas IX-A SMP Negeri 13 Surabaya Untuk Meningkatkan Minat Belajar - Kevin Geralda Adhianto; Andhega Wijaya; Agus Suparno (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This research aims to explain the use of learning video media in increasing the learning interest of class IX-A students at SMP Negeri 13 Surabaya in the subjects of Physical Education, Sports and Health. The type of research carried out was classroom action research (PTK), with a qualitative approach. The subjects of this research consisted of 31 students. The instruments used include observation sheets and questionnaires to measure students' interest in learning. Student activity data was obtained through these two instruments. The results of measuring students' learning interest in cycle I showed unsatisfactory results. However, in cycle II, there was a significant increase in interest in learning and it was categorized as successful. Thus, it can be concluded that the application of learning video media is effective in increasing the learning interest of class IX-A students at SMP Negeri 13 Surabaya in learning PJOK.